Penggunaan Tembang Macapat dalam penyebaran Islam di Jawa - Fadhilla Ainuraziza Ramadhanti; Lutfiah Ayundasari (Universitas Negeri Malang, 2021)
Islam is developing in Java Island very fast. This was assisted by the presence of walisongo who spread Islam throughout Java to outside Java. Many saints use art as a medium of preaching. One of the media used to spread Islam at that time was by using the macapat song. Macapat songs, which are praise to God, convey teachings about Islam, as well as an invitation to a better life. Therefore in this article the author aims to: 1) explain about the macapat song, 2) explain the various macapat songs and their reasons, 3) explain how the macapat song is used in the spread of Islam in Java. Islam berkembang di Pulau Jawa dengan sangat cepat. Hal ini dibantu dengan adanya para walisongo yang menyebarkan Islam ke seluruh penjuru Jawa hingga luar Jawa. Banyak para wali yang menggunakan kesenian sebagai media dakwahnya. Salah satu media yang digunakan untuk menyebarkan Islam saat itu ialah dengan menggunakan tembang macapat. Tembang macapat yang merupakan pujian kepada Tuhan, menyampaikan ajaran-ajaran tentang Islam, serta ajakan untuk ke kehidupan yang lebih baik. Oleh karenya dalam artikel ini penulis bertujua untuk: 1) menjelaskan tentang tembang macapat, 2) menjelaskan macam-macam tembang macapat beserta makanya, 3) menjelaskan bagimana tembang macapat digunakan dalam penyebaran Islam di Jawa.